MXene conductive binder for improving performance of sodium-ion anodes in water-in-salt electrolyte. (January 2021) - Malchik, Fyodor; Shpigel, Netanel; Levi, Mikhael D.; Penki, Tirupathi Rao; Gavriel, Bar; Bergman, Gil; Turgeman, Meital; Aurbach, Doron; Gogotsi, Yury
Abstract: While many studies have been devoted to the development of new active materials for Na-ion aqueous batteries, much less attention has been given to the binders and other passive components, which largely determine the battery performance. This study demonstrates a beneficial use of MXene as a highly efficient binder for Na-ion anodes operating in aqueous electrolyte solutions. The high conductivity of 2D titanium carbide (Ti3 C2 T x ; T = terminal groups, mostly –OH, 0 < x < 2) denoted as MXene and the strong attractive interactions between its sheets and active material particles enable their effective encapsulation providing electronically conductive paths, fast ion transfer, and capacitive contribution to the stored charge. Using highly concentrated NaClO4 as an electrolyte solution providing a stable potential operation window, successful integration of NaTi2 (PO3 )4 (NTP) particles with MXene as a binding agent has been achieved. The integrated NTP/MXene electrodes show superior electrochemical performance in terms of capacity, rate capability, and long-term stability compared to the conventional polyvinylidene difluoride-bonded electrodes. The fabricated anodes containing 20 wt% Ti3 C2 T x binder showed high rate capability with capacities of 98, 94, 91, 87, and 83 mAh/g at 2, 5, 10, 15 and 20 C rate, respectively, as well as the cycling efficiency of more than 99.1%. A full cell comprised of a Na-intercalated MXene/NTP anode and a FeFe(CN)6 cathode operating in a NaClO4 electrolyte solution is demonstrated with the maximal charging potential of 2 V and a potential of 1.2 V at 50% depth of discharge. Graphical Abstract: ga1 Highlights: The use of 2D MXene (Ti3 C2 T x ) sheets as a highly effective binder for aqueous anodes was demonstrated. Binding properties of the MXene flakes enables successful fabrication of free-standing anodes up to 80 wt% of NaTi2 (PO4 )3 . The NTP/MXene anode shows a superior energy density, rate capability, and cycling stability compared to the NTP-PVdF system.